Human-computer interaction–INTERACT 2015 : 15th IFIP TC 13 International Conference, Bamberg, Germany, September 14-18, 2015 : proceedings /: 15th IFIP TC 13 International Conference, Bamberg, Germany, September 14-18, 2015 : proceedings. ([2015]) - Unknown
No abstract available